KRITIK IBN WARRAQ ATAS ORIENTALISME EDWARD SAID: PERDEBATAN EPISTEMOLOGIS MENGENAI ‘TIMUR DAN BARAT’ - Media Zainul Bahri (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This article tries to describe Ibn Warraq's critique onEdward Said's monumental work, "Orientalism (1979)" in four main areas; Said anti-Western; misunderstanding on Western culture; orientalism and imperialism; and the relationship of Western music with the Eastern world. Based on critical study approach to the two monumental works of thesetwo intellectual figures, the results of the study show that even Said has never "responded" to Warraq's criticism directly, but Said's views and thoughts after his publication of the work "Orientalism", had become a kind of "defense" and "weapons", which counterattacked to his critics. Said's thesis against Warraq's anti-thesis, which later led to synthesis, and likewise the circulation of theory and theoretical criticism, has made a very significant contributionto the development of science. Through a very serious academic debate between Warraq and Said, the perspectives of scientists and people in generalhave become clearer.